ENGLISH LANGUAGE DIASPORA AND THE HIT-AND-MISS EXPERIMENTATION WITH ENGLISH CURRICULUM IN BANGLADESH - Haque, Mr. Md. Azizul (International Journal of Language Education, 2017)
Despite the common diasporic origin English in Bangladesh is neither a native nor a second language, but a foreign language, in countries like India and Pakistan, English is used as the second language. The chronological history of English in Bangladesh has both political as well as social elements, which influence the learning of English at every level of education. In the mid-90s there was a growing demand from the educationists in the country to change the English curriculum as per ‘needs analysis’, and the curriculum is restructured aligning with the communication needs and the syllabus was largely transformed into a communicative one. Yet research explores that the needs are not served for the learners tend to by-pass the cognitive part of the language learning—thus failing to communicate properly. Now, in the second decade of the new millennium English curriculum along with other subjects has been made ‘creative’ at pre-tertiary level, but debates are still on to evaluate whether the system complies with the current practices prevailing within the institutional premises. The total picture thus presents a very confusing answer to the questions why all these efforts are being futile and why the English language teaching fails to touch the three main domains of learning—the cognitive, the affective and the psychomotor. The current study wants to explore whether such experiments with the curriculum and the dilemma of receiving or rejecting the idea of acculturation with largely an anti-colonial mindset hinder the desired performance of the language.